Influence of magnetic field alignment and defect concentration on nitrogen-vacancy polarization in diamond. (24th December 2015) - Drake, M; Scott, E; Reimer, J A
Abstract: We present a quantitative, systematic study of the polarization of the Zeeman magnetic sublevels of the NV-defect in diamond as a function of magnetic field alignment relative to the NV-defect axis. The orientation dependence of NV-polarization in the lab frame is accounted for by a Wigner rotation of a constant defect frame polarization. We also find that the NV-defect level polarizations vary with the P1 defect concentration, and that the polarization of the m s = 0 state with optical pumping decreases from 46% to 36% in samples as P1 concentrations vary from 20 ppm to 100 ppm, respectively.